The Influence of Government Financial Report Accountability on The Achievement of SDGS 1 in Indonesia - Sella Sella; Muhammad Iqbal; Mustamin Mustamin; Andi Chairil Furqan (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of government financial report accountability on the achievement of Sustainable Development Goals (SDGs) 1 in Indonesia. The study used secondary data obtained from the Central Statistics Agency (BPS) and the Supreme Audit Agency (BPK). The study sample consisted of 456 local governments with an observation period of 2021–2022, resulting in 912 observations. The analytical method used was panel data regression with the Generalized Least Squares (GLS) approach and the Random Effects Model (REM). The results showed that government financial report accountability has a positive and significant effect on the achievement of SDG 1. The coefficient value of 0.645 with a significance level of 0.000 indicates that the better the level of local government accountability, the higher the achievement of poverty alleviation. This study proves that transparent, accountable, and effective financial governance can support the success of government programs in improving public welfare and accelerating the achievement of sustainable development in Indonesia.